KARAKTERISASI SENYAWA ISOPRENOID SEBAGAI PRODUK ALAMI PADA MANGROVE SEJATI MINOR NON SEKRESI Excoecaria agallocha L., DI HUTAN MANGROVE SUMATERA UTARA - Hasbi Nurainun Nurainun; Mohammad Basyuni; Lollie Agustina (Peronema Forestry Science Journal, 2012)
Characterization of isoprenoid compounds for natural products on true mangrove minor non-secreting Excoecaria agallocha L. in North Sumatran mangrove forest. This study aims to determine the characterization of isoprenoid compounds and lipid content of the mangrove type of non-secretion (Excoecaria agallocha L.) The samples were collected from the leaves and roots of   E. Agallocha L. The results showed the composition NSL of E. agallocha L. were squalen, campesterol, stigmasterol, β-sitiosterol, cycloarterol, taraxerol, β-amyrin, germanicol, lupenone, betulin, lupeol, and α-amyrin. Stigmasterol is part of phytosterol had the highest content of 13.2. This research may provide information the diversity of triterpenoid and phytosterol composition in North Sumatran mangrove E. Agallocha L. Keywords: Mangrove, E. Agallocha (L), NSL and lipid.